(3UaI QShd Gddg Udi Gddg Ydjg hSdes - (3Ydj Hf CHj WGdH,J (B40 (3g` s
(3ChdgG (B:s
(3gPg UaI ai hUa QShd Gddg Udi Gddg Ydjg hSde bGd Ydi Hf CHj WGdH jG CHG gQjQI Ef QShd QH GdYGdejf CUdg BOei hMSHg CHQGgjei s
(3BNQgG (B:s
(3LYdg Gddg QShdkG cQjekG QMjekG hai gjfjI fhQ hai bOejg Edi COfjg fhQ hai dMjjg cKGa hHjf cJajg NGJe GdfHhI ecJhHkG Ydjg (B: (3dG Edg EdG Gddg eMeO QShd Gddg Udi Gddg Ydjg hSde s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3QhGjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B139 s
Keywords: (3GdJGQjNs